Increasing Productivity of Creative Industry MSMEs in the MEA Era by Utilizing Appropriate Technology (TTG): Peningkatan Produktifitas UMKM Industri Kreatif di Era MEA dengan Pemanfaatan Teknologi Tepat Guna (TTG) - Budi Gunawan; Sri Mulyani; Fajar Nugraha (Yayasan Ahmar Cendekia Indonesia, 2022)
In the MEA era, Indonesia and nine other ASEAN countries had the same opportunity to take advantage of integrated markets in one region. Because it is already in force, there is no other choice for people in ASEAN countries, including the business world, both large and micro, small and medium business (MSME) segments, in addition to being prepared to face the ASEAN open market. If MSMEs are placed in the market freely, their survival will be determined by the market, and with its various limitations, it will certainly be difficult to compete with business actors who are part of the global conglomerate network. For this reason, support and assistance from all elements are needed, both the government and academics in improving the competitiveness of MSMEs to developments in this open market arena. One of the SMEs engaged in the creative industry is